Jurister och språkkonsulter i samarbete på Skatteverket - Hultberg, Maria; Wassdahl, Louise (Klart språk i Norden, 2015)
Skatteverket övergår från att ha sin rättsinformation i tryckta handledningar till att publicera den på webben. Samtidigt som all text digitaliseras bearbetar man informationen enligt klarspråksprinciper. Språkkonsulter, sakkunniga skribenter och rättssäkrare har arbetat nära tillsammans med ansvar för språket respektive sakinnehållet. Vi språkkonsulter fick makten att förändra det traditionstyngda juridiska språket. Har vi förvaltat den makten väl? Vi har lärt oss att jurister och språkkonsulter kan ha mycket olika syn på vad som är tydlig text men vi tycker att vi gemensamt åstadkommit klarspråk för mottagaren. Det ser inte längre ut som äldre tiders juridiska språk men inte heller som klarspråk som riktar sig till allmänheten. Summary The Swedish Tax Agency is converting approximately 20 printed manuals containing its interpretations of the Swedish tax laws for access from a central web site. During the digitising process the language on every single page has been reviewed and edited into plain language. Plain language consultants and tax law experts have been working closely together, the former taking responsibility for the language and the latter for the complex content. As linguistic experts we have the power to influence the heavy and sometimes stilted language, a language often marked by old legal tradition. Have we used our power well? We have learned that linguists and lawyers can have very different views on what is clear, and on what constitutes plain language. However, we think that, by pooling our resources, we have achieved a good compromise, aimed at a target audience that has a good knowledge of the tax laws, with the purpose of guiding them in their complicated tasks.